2009
DOI: 10.1111/j.1365-2389.2009.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil metaproteomics: a review of an emerging environmental science. Significance, methodology and perspectives

Abstract: SummarySoil is a dynamic system in which microorganisms perform important tasks in organic matter transformations and nutrient cycles. Recently, some studies have started to focus on soil metaproteomics as a tool for understanding the function and the role of members of the microbial community. The aim of our work was to provide a review of soil proteomics by looking at the methodologies used in order to illustrate the challenges and gaps in this field, and to provide a broad perspective about the use and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 78 publications
1
79
0
Order By: Relevance
“…1). As with metagenomics and metatranscriptomics, there has been a steady evolution of the methodology for the extraction and analysis of proteins from soils (Bastida et al, 2009;Hettich et al, 2012;Siggins et al, 2012). Nonetheless, the extraction of proteins lags behind that of nucleic acids, in part because of the strong interactions between proteins and other organic molecules and inorganic minerals in soils (Adamczyk et al, 2008; Kleber et al, 2007).…”
Section: Metaproteomicsmentioning
confidence: 99%
“…1). As with metagenomics and metatranscriptomics, there has been a steady evolution of the methodology for the extraction and analysis of proteins from soils (Bastida et al, 2009;Hettich et al, 2012;Siggins et al, 2012). Nonetheless, the extraction of proteins lags behind that of nucleic acids, in part because of the strong interactions between proteins and other organic molecules and inorganic minerals in soils (Adamczyk et al, 2008; Kleber et al, 2007).…”
Section: Metaproteomicsmentioning
confidence: 99%
“…Metaproteomic studies of rhizosphere samples are still at its beginning and first reports were only published very recently Wu et al, 2011). In those studies, proteins were directly extracted from rhizosphere samples (without a preceding physical enrichment step of microbial cells; Bastida et al, 2009), separated by twodimensional gel electrophoresis and identified by MALDI-TOF/TOF. The studies revealed that a direct protein extraction method restricted microbial protein identification in the rhizosphere samples by the high recovery of plant proteins (475% from 120 different identified proteins).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the changes in protein pattern might indicate that the community structure of soil microorganisms and their physiological activities were modified significantly under pollutants stress [15]. These low molecular weight proteins could be related to the presence of PCBs and could be a microbial response to organic pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the emergence of soil proteomics could offer us a new perspective to solve the problem [15]. Proteins are the major actors in organism metabolism process, and they fall into a variety of categories; for example, enzymes are proteins with a catalytic function.…”
Section: Introductionmentioning
confidence: 99%